Pengaruh Tingkat Return Sertifikat Bank Indonesia Syariah (SBIS) Terhadap Penempatan Pada SBIS dan ROA Bank Umum Syariah di Indonesia - Kawiryawan, Naroh; Hapsari, Meri Indri (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
In order to fulfill the need of banking industry that grew rapidly, Bank Indonesia createÂ several monetary instrument. One of them is Islamic Certificate of Bank Indonesia (SBIS). ThisÂ research aims to investigate the effect of return rate of SBIS to investment in SBIS and also theÂ profitability of sharia commercial banks in Indonesia. The research method used is pathÂ analysis with three kind of variables, which is SBISâs return rate as exogenous variable,Â investment in SBIS as intervening endogenous variable, and the profitability as endogenousvariable.The result of this research shows that SBISâs return rate effects significantly positive to theÂ investment in SBIS, but effects unsignificantly negative to the probability of sharia commercialÂ banks. Meanwhile investment in SBIS has non-significantly positive effect to the profitability ofÂ sharia commercial banks.